Administrative judiciary oversight of disguised penalties - Hamd, Mariwan Saber (Journal of Legal and Political Studies, 2019)
The administration has the discretionary authority to take internal administrative measures against the employee in order to achieve the public interest, and sometimes the administration is used this discretionary authority to punish an official employee, adding a punitive nature to internal administrative procedure and turning it into disguised punishment. This study has been devoted to research to administrative judiciary’s control over the disguised punishments,as there is a deviation authority in decisions that involving disguised punishment with attention the administrative judiciary when its exercise control over legitimacy of administrative decisions concerning employee. By the extrapolation of the administrative judiciary’s provisions, the study focused on the standards that built by the administrative judiciary in Iraq and the Kurdistan Region-Iraq to reveal the disguised punishments, where the administrative judiciary addressed many of the appeals against the administrative decisions contained disguised punishment as contrary to the civil service rights of the public employee.
Keywords: discretionary authority; internal administrative measures; disguised punishment; administrative judiciary; legitimacy